Pengaruh Gender Terhadap Kualitas Laporan Keuangan Pada Perusahaan Manufaktur Terdaftar Di Bursa Efek Indonesia - Sriyunia Anizar; Maria Anastasia; Adi Rahman; Jaya Bahwi Yanti (Politeknik Ganesha Medan, 2023)
The purpose of this study is to examine the effect of gender equality on the quality of financial statements as a proxy for the auditor's opinion. This research is a quantitative associative study with units of analysis of audited financial statements and independent auditor reports issued by KAP. This study used secondary data, data analysis techniques used logistic regression with SPPS version 26 software. The sample selection used a purposive sampling method. The results of the study show that the board of committees and the board of directors have no influence on the quality of financial reports. The gender equality variable represented by the audit committee board is proven to have no effect on the quality of the financial statements as a proxy for the auditor's opinion. This means that the availability or unavailability of women on the audit committee board does not affect the opinion that will be issued by the auditor. The gender equality variable represented by the board of directors has proven to have no effect on the quality of the financial statements as proxied by the auditor's opinion. This means that the availability or unavailability of women on the board of directors does not affect the opinion that will be issued by the auditor.